Cultural extinction in evolutionary perspective. (23rd April 2021) - Zhang, Hanzhi; Mace, Ruth
Abstract: Abstract: Cultural diversity is disappearing quickly. Whilst a phylogenetic approach makes explicit the continuous extinction of cultures, and the generation of new ones, cultural evolutionary changes such as the rise of agriculture or more recently colonisation can cause periods of mass cultural extinction. At the current rate, 90% of languages will become extinct or moribund by the end of this century. Unlike biological extinction, cultural extinction does not necessarily involve genetic extinction or even deaths, but results from the disintegration of a social entity and discontinuation of culture-specific behaviours. Here we propose an analytical framework to examine the phenomenon of cultural extinction. When examined over millennia, extinctions of cultural traits or institutions can be studied in a phylogenetic comparative framework that incorporates archaeological data on ancestral states. Over decades or centuries, cultural extinction can be studied in a behavioural ecology framework to investigate how the fitness consequences of cultural behaviours and population dynamics shift individual behaviours away from the traditional norms. Frequency-dependent costs and benefits are key to understanding both the origin and the loss of cultural diversity. We review recent evolutionary studies that have informed cultural extinction processes and discuss avenues of future studies.